Akurasi dalam Mengidentifikasi Tingkat Similarity pada Artikel Ilmiah Menggunakan Algorithma Jaro Winkler - Firman Santosa (Jurnal Informasi dan Teknologi, 2022)
Plagiarism is an issue that often develops and always occurs, especially in universities. STKIP Rokania already has a scientific article recording system called E-Jurnal which is always used by lecturers to publish journals and search for relevant topics and literature. In making scientific articles, plagiarism is often not detected in scientific articles submitted by lecturers. This fraud is carried out by combining the available abstracts to form one abstract resulting from the merger. This means that the abstract is not the result made by the researcher himself. The biggest problem is when this fraudulent act is not detected, which is due to manual checking of documents. This of course can result in lowering the reputation of the accredited E-Journal. Of course, this problem must be immediately given the right solution to identify the level of similarity in scientific articles that already exist. Identification of the level of similarity in scientific articles is made through a structured development stage using the Jaro Winkler algorithm which is chosen to detect the similarity of abstract documents of scientific articles with abstracts that have been stored in the E-Jurnal database. The system will display the percentage level of similarity of the abstract of the scientific article so that the journal admin makes the right decision when accepting the scientific article or rejecting it. Through this research, lecturers can do an initial check of abstracts from prospective scientific articles to minimize plagiarism. Thus, it can minimize the actions of lecturers' fraud in making scientific articles and produce high-quality journals of higher value.